Manajemen Integrasi Kurikulum International Middle Year Curriculum (IMYC) dan Kurikulum Nasional dengan Perspektif Inklusi di SMP Tumbuh Yogyakarta - Sri Aryaningsih; Rejokirono Rejokirono (Media Manajemen Pendidikan, 2022)
The research objectives include (1) Analyzing the management of the IMYC curriculum integration and the national curriculum with an inclusive perspective at SMP Tumbuh Yogyakarta; (2) Analyzing the role of educational inputs, processes, and outputs on the successful implementation of the IMYC curriculum integration and the national curriculum with an inclusive perspective at SMP Tumbuh Yogyakarta; (3) Analyzing the strength of integrating the IMYC curriculum and the national curriculum with an inclusion perspective at SMP Tumbuh Yogyakarta. This research uses a qualitative approach with a case study research design. This research was conducted in the international class of SMP Yogyakarta. Data was collected by means of in-depth interviews, observation, and documentation. The research subjects were the foundation administrator, head of school committee, principal, international curriculum coordinator, national curriculum coordinator, IMYC subject teachers, guidance and counseling teacher, and support teachers. The data analysis technique was carried out by data reduction, data presentation, and drawing conclusions/verification. The results showed that: (1) SMP Yogyakarta implemented a curriculum management function in its management, starting from planning, organizing, implementing, and controlling the curriculum with various strategies, for example using the Integrated Curriculum model at the school level by integrating the national curriculum and IMYC and enriched with Cambridge curriculum specifically for Mathematics, Science and English. At the subject level using the Integrated Curriculum model for IMYC subjects and Separate Subject Curriculum for National Curriculum subjects; (2) The development of this curriculum integration model requires the role of educational inputs, processes, and outputs to support the achievement of curriculum success and the expected quality of education; (3) The advantages of this model are shown in the learning age which facilitates the learning needs of 11-14 years old, international thinking and international learning (International Mindedness and International Learning) insight, as well as the ability of students who are accustomed to diversity.